THE ROLE OF POSITIVE TEMPERATURE GRADIENT IN WOOD DRYING (Innovation in Woodworking Industry and Engineering design, 2026)
This study investigates the theoretical and technological aspects of concrete methods for wood drying in positive temperature gradient condition. Accelerated water movement from central wood layers to surface creates conditions for faster and better quality drying. It was explained four events when is possible benefit a similar condition: high-frequency drying, microwave drying, vacuum drying and by cyclic convective regimes.